An Entrapped Epidural Catheter in a Postpartum Patient. Issue 6 (November 1998) - Jongleux, Elizabeth F.; Miller, Robert; Freeman, Anthony
Abstract : Background and Objectives: Epidural catheters are seldom difficult to remove from patients. In fact, a review of the literature demonstrates only a few cases pertaining to epidurals and the unusual complication of catheter entrapment. Methods: This case report involves an uncomplicated obstetric patient who had an epidural placed for labor and in whom multiple attempts were needed to remove the catheter.